Service infrastructure sharing of resettlers and host communities a case study of the Kasiglahan Vilage 3 (KV-3) Summerfield Subdivision in Trece Martires, Cavite - Marcelo, Rosalyn-Frances Osorio (2007)
This study aims to provide some ideas for resettlement planning, particularly in the aspect of integrating resettlers and hosts through service infrastructure sharing...